Policing insecurity : police reform, security, and human rights in Latin America - Uildriks, Niels A. (Lexington Books, 2009)
Profound distrust commonly characterizes not only the relationship between citizens and state institutions, but also social, as well as inter- and intra-state relations. This impacts the effectiveness and quality of the service provided by state institutions. The degree to which police and judicial reforms are able to generate trust on these fronts is therefore an important yardstick to judge their relevance under varying circumstances of 'post-authoritarian rule', but this question is largely ignored inthe current literature on policing and reform. From this perspective, Policing Insecurity.